Estetika Panca Suaradalam Upacara Yadnya di Bali - I Putu Ariyasa Darmawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
One form of offering to God Almighty is the use of the Panca Suara element in every yajña ceremony in Bali. To obtain valid data, this article uses literature study, by examining books, similar scientific articles, and references related to theology and aesthetics of Panca Suara. The five voices are the five voices that must be present in every yajña ceremony. The five sounds are: 1) the sound of a genta, 2) the sound of a mantra, 3) the sound of song or kekawin, 4) the sound of unemployment or gamelan, 5) the sound of kulkul or sunari. Panca Suara cannot be separated from the aesthetic concepts of Hindu Satyam, Siwam, and Sundaram. Each sound that is generated has the meaning of worship of a certain god and has powers such as Sang Hyang Smara Ratih, Panca Brahma, Panca Bhuta, and Panca Dewata, Catur Loka Phala. The sacredness of this sound is indicated by a special ritual before using these sounds. Panca Suara that is present in every religious ceremony in Bali, is not only as entertainment and complementary, but has magical values that can vibrate the atmosphere. The sacredness of these sounds is indicated by the existence of several rituals that must be performed to initiate these sounds, so as to convey the intent of the community to the power worshiped in the temple.